2012
DOI: 10.1007/s00737-012-0312-0
|View full text |Cite
|
Sign up to set email alerts
|

Mother–infant bonding impairment across the first 6 months postpartum: the primacy of psychopathology in women with childhood abuse and neglect histories

Abstract: Purpose Our goal was to examine the trajectory of bonding impairment across the first 6 months postpartum in the contexts of maternal risk, including maternal history of childhood abuse and neglect and postpartum psychopathology, and to test the association between self-reported bonding impairment and observed positive parenting behaviors. Method In a sample of women with childhood abuse and neglect (CA) histories (CA+, n=97) and a healthy control comparison group (CA-, n=53), participants completed question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
168
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(186 citation statements)
references
References 43 publications
13
168
1
4
Order By: Relevance
“…Also, similarly to the current study, Muzik et al (2013) found a general increase in the mother-infant bonding quality over the first six months postpartum irrespective of risk status (e.g. mental health problem), but longitudinal research of the trajectory of both parents' bonding with their baby past this early period remains sparse.…”
Section: Journal Of Reproductive and Infant Psychology 451supporting
confidence: 47%
See 1 more Smart Citation
“…Also, similarly to the current study, Muzik et al (2013) found a general increase in the mother-infant bonding quality over the first six months postpartum irrespective of risk status (e.g. mental health problem), but longitudinal research of the trajectory of both parents' bonding with their baby past this early period remains sparse.…”
Section: Journal Of Reproductive and Infant Psychology 451supporting
confidence: 47%
“…Paternal depression has also been shown to have negative effects on the parenting behaviours of fathers (for a meta-analysis, see Wilson & Durbin, 2010). Some evidence suggests bonding difficulties may also arise in parents suffering from childbirth-related PTSD (Muzik et al, 2013;Nicholls & Ayers, 2007;Parfitt & Ayers, 2009). However, longitudinal research of parent-baby bonding that incorporates the father as well as the mother, including a range of mental health variables remains sparse.…”
Section: Parental Mental Healthmentioning
confidence: 99%
“…Emotional abuse has the most negative effect on a child’s development (Allen, 2011; Glaser, 2011; Iwaniec, Larkin, & Higgins, 2006), and is that form of abuse most likely to influence one’s own parenting in a variety of negative ways (Banyard, Williams, & Siegel, 2003; Muzik et al, 2013; Steele et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…This could be due to various methodological differences, such as the use of different PTSD measures and heterogeneity of studied populations and geographical locations. Furthermore, the mean prevalence of perinatal PTSD in high-risk samples might be influenced by the particularly high prevalence rates reported in a few studies (Ammerman et al, 2012;Horsch et al, 2015;Muzik et al, 2013). Finally, this review might be affected by publication bias, which may arise from language restriction and the relative lack of publications from non-western countries.…”
Section: 1methodological Issuesmentioning
confidence: 99%